2021
DOI: 10.1002/yea.3524
|View full text |Cite
|
Sign up to set email alerts
|

dnm1 deletion blocks mitochondrial fragmentation in Δfzo1 cells

Abstract: Mitochondrial division and fusion play critical roles in maintaining functional mitochondria. Fzo1 is an outer mitochondrial membrane GTPase that played an essential role in mitochondrial fusion in budding yeast Saccharomyces cerevisiae. Here, we report the characterization of the Schizosaccharomyces pombe homologue of S. cerevisiae Fzo1p, Fzo1. Disruption of the fzo1 gene in S. pombe results in a fragmented mitochondrial morphology and a dramatically reduced growth on glycerol medium phenotype, indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…This result is similar to the one reported recently that mitochondria become tubular upon deletion of both dnm1 and fzo1 [14]. It was shown that mitochondrial morphology depends on the order of the deletion of dnm1 and fzo1 [14]. That is, mitochondrial morphology of dnm1 Δ fzo1 Δ cells is similar to the one of dnm1 Δ cells if dnm1 is deleted first, whereas mitochondrial morphology of dnm1 Δ fzo1 Δ cells is wild type‐like if fzo1 is deleted first [14].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This result is similar to the one reported recently that mitochondria become tubular upon deletion of both dnm1 and fzo1 [14]. It was shown that mitochondrial morphology depends on the order of the deletion of dnm1 and fzo1 [14]. That is, mitochondrial morphology of dnm1 Δ fzo1 Δ cells is similar to the one of dnm1 Δ cells if dnm1 is deleted first, whereas mitochondrial morphology of dnm1 Δ fzo1 Δ cells is wild type‐like if fzo1 is deleted first [14].…”
Section: Resultssupporting
confidence: 92%
“…1 and 2). Our finding is consistent with the one reported recently that deletion of both dnm1 and fzo1 restores tubular mitochondrial morphology and restores cell growth on nonfermentable medium [14]. Therefore, it seems that mitochondrial morphology is a key factor in dictating mitochondrial functionality in fission yeast cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Taking these results into account, in order to improve the stability of endogenous 2µ-based expression vector in yeast, an essential gene could be introduced into the plasmid while knocking out the same essential gene in the genome to ensure the existence of engineered endogenous 2µ plasmid in yeast (Zeng et al, 2021). In the future, researchers could apply the CRISPR/Cas9 system to directly integrate metabolic pathways into the endogenous 2µ plasmid with an essential gene in vivo (Dean-Johnson and Henry, 1989;Zheng et al, 1993;Wang et al, 2020;Yang et al, 2021). In summary, our endogenous 2µ-based expression vector p2µM has improved stability than the commonly used YEp pRS423, so it could be applied in S. cerevisiae for genetic manipulations.…”
Section: Discussionmentioning
confidence: 99%